Diante de Godard: história, imagem e multiplicidade temporal - Silva, Henrique Martins da (2019)
This research has as object the temporal multiplicity of the image from the cinematographic production of Jean-Luc Godard. It is a question of thinking the temporal multiplicity of history through the filmic images produced by the filmmaker to his way of making movies. This one that innovated in its time when giving protagonism and to show that it was possible to write with the camera. The moving image, the assembly and the own thinking with images in the work of Godard reveal to us multiple layers of heterogeneous times that elucidates the affirmation of the philosopher and historian of the art Georges Didi-Huberman that "when before the image, we are before the time" . Thinking about the multiple times of the image in the cinematographic field implies recognizing its discontinuities and different rhythms as the image "will survive" for the sake of holding more experience and expectation than the being who observes it. Thus, the strata of time described by the German historian Reinhart Koselleck refer not only to the past, but also to the future that opens up as a possibility / projection. In this way, both Didi-Huberman and Koselleck help us to understand Godard's complex time-frame.